1998
DOI: 10.1016/s0002-9440(10)65662-3
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Instability and Mutation of DNA Mismatch Repair Genes in Gliomas

Abstract: Microsatellite instability (MSI) has been identified in various human cancers , particularly those associated with the hereditary nonpolyposis colorectal cancer syndrome. Although gliomas have been reported in a few hereditary nonpolyposis colorectal cancer syndrome kindred , data on the incidence of MSI in gliomas are conflicting , and the nature of the mismatch repair (MMR) defect is not known. We established the incidence of MSI and the underlying MMR gene mutation in 22 patients ages 45 years or less with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 44 publications
3
69
0
1
Order By: Relevance
“…The M6P/IGF2R also contains a poly-G region that is a common target for frame-shift mutations in colon, gastric, endometrial and liver tumors with mismatch repair de®ciencies and microsatellite instability (MI) (Ouyang et al, 1997;Yamada et al, 1997). Moreover, the M6P/ IGF2R is mutated in human gliomas that do not contain mutations in the TGFb type II receptor or Bax genes (Leung et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…The M6P/IGF2R also contains a poly-G region that is a common target for frame-shift mutations in colon, gastric, endometrial and liver tumors with mismatch repair de®ciencies and microsatellite instability (MI) (Ouyang et al, 1997;Yamada et al, 1997). Moreover, the M6P/ IGF2R is mutated in human gliomas that do not contain mutations in the TGFb type II receptor or Bax genes (Leung et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…We searched for the inactivation of the MMR genes causing severe MSI in the two gliomas and found a germline mutation and promoter methylation of the hMLH1 gene. Germline mutations of the hMLH1, hPMS2 and hMSH2 genes in lymphocyte DNAs of the patinents with Turcot's syndrome have been demonstrated previously (Hamilton et al, 1995;Miyaki et al, 1997;Leung et al, 1998).…”
Section: Discussionmentioning
confidence: 96%
“…Leung et al also reported that four of 22 malignant gliomas (WHO grade III or IV) with onset at less than 45 years of age, carried germline mutations of the hMLH1 or hMSH2 genes (Leung et al, 1998). Further detection of this type of tumor and analyses of causative mutations or methylation of the hMLH1 gene as well as other genes involved in MMR should cast new light on the genesis of early onset human glioblastomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6,8 The gene contains a poly-deoxyguanine (poly-G) region that is a common mutational target in colon, gastric and endometrial tumors with mismatch repair deficiencies and microsatellite instability. [15][16][17] It is also mutated in human gliomas that do not contain mutations in either the transforming growth factor b type II receptor or Bax genes. 17 Moreover, the M6P/IGF2R is mutated in 30% of breast tumors and 60% of squamous cell carcinomas of the lung.…”
Section: Introductionmentioning
confidence: 99%